Methodological proposal for energy biomass market characterization, the case of the Costa Rican rice - Brenes-Peralta, Laura Patricia (2022)
Energy production is commonly linked to high environmental costs. The agri-food sector is considered one of the most unbalanced sectors of the economy regarding energy intake and output; however, it also entails opportunities for cleaner energy production. Within such kind, the interest in bioenergy has grown; therefore, this study had the aim to propose a methodological framework for the characterization of the energy biomass market. The proposal uses methods such as literature reviews, surveys and statistical analysis. As a result, the proposed framework consists of the following steps: a) sector data collection, including technical biomass parameters, b) evaluation of the degree of knowledge of the market actors in regards to those parameters, c) the analysis of the perception of the actors in regards to the energy biomass market, and d) the definition of variables affecting the energy biomass market. The framework was applied to the Costa Rican rice agri-food chain as a case study and validation process. Potentially, 1.217.544 t of rice biomass obtained annually from husk and plant residues is fit for energy production. Moreover, the actors show relevant knowledge of technical parameters, perceive the market as stable, and define the volume and biomass homogeneity as determinant market variables. The obtained information is considered of interest for adequate market characterization and further strategic planning for bioenergy production.